2019
DOI: 10.5194/tc-2019-134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating The Sea Ice Floe Size Distribution Using Satellite Altimetry: Theory, Climatology, and Model Comparison

Abstract: Abstract. In sea-ice-covered areas, the sea ice floe size distribution (FSD) plays an important role in many processes affecting the coupled sea-ice-ocean-atmosphere system. Observations of the FSD are spare – traditionally taken via a pain-staking analysis of ice surface photography – and the seasonal and inter-annual evolution of floe size regionally and globally is largely unknown. Frequently, measured FSDs are assessed using a single number, the scaling exponent of the closest power law fit to the observed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Its main characteristic is certainly its cut-off floe size that depends both on sea ice properties and on the wave field. This redistribution scheme could easily be adapted in case progress were made on the relative importance of the parameters affecting this cut-off floe size and the associated redistribution, either from observations thanks to new available FSD datasets (Hwang et al, 2017;Horvat et al, 2019), or from discrete element modelling (Herman, 2018). Note also that alternatives exist to the redistribution scheme of Zhang et al (2015), and in particular the one suggested by Horvat and Tziperman (2015) that makes use of the whole wave frequency spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Its main characteristic is certainly its cut-off floe size that depends both on sea ice properties and on the wave field. This redistribution scheme could easily be adapted in case progress were made on the relative importance of the parameters affecting this cut-off floe size and the associated redistribution, either from observations thanks to new available FSD datasets (Hwang et al, 2017;Horvat et al, 2019), or from discrete element modelling (Herman, 2018). Note also that alternatives exist to the redistribution scheme of Zhang et al (2015), and in particular the one suggested by Horvat and Tziperman (2015) that makes use of the whole wave frequency spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum-likelihood estimation (MLE) was used to estimate the most probable value of α and the most probable onset (if any), A 0 , of power-law behavior in the area distribution. The MLE estimation was performed for each sub-region (n = 13), physiographic terrain class (n = 5), and over the entire dataset [56][57][58]. To understand how the choice of sub-region boundary might have influenced sampling, a bootstrap method [59] was used to estimate p-values and one-standard-deviation confidence intervals for α and A 0 as follows: 1000 subsets for A > A 0 were generated using the MLE estimates of α.…”
Section: Power-law Scaling Of Water Body Area Distributions Within Phmentioning
confidence: 99%